Coliform density in oyster culture waters and its relationship with environmental factors - Mignani, Luciene; Barbieri, Edison; Marques, Helcio Luis De Almeida; Oliveira, Ana Julia Fernandes Cardoso De [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the total and thermotolerant coliform densities in the oyster culture water of Cananeia, SP, Brazil, correlating these densities with environmental variables and tidal variations. Superficial water samples were collected in two tide conditions (spring and neap) from three areas of Cananéia municipality (Mandira, Itapitangui and Cooperostra). The three studied areas showed good conditions for the culture regarding coliform densities. The two tidal conditions differed significantly as to total coliform concentration; however, the same procedure was not performed for thermotolerant coliforms. No correlation was observed between water temperature, pH, and concentrations of total and thermotolerant coliforms. Coliform density was positively correlated with rainfall and negatively correlated with salinity. Spring and neap tides differed significantly as to coliform number. Simple diagnosis of environmental conditions of the crop fields is insufficient to assess water quality of shellfish cultivation. A continuous monitoring program of planted areas is necessary both for the assessment of water quality potential for marine culture and for ensuring safe consumption of seafood, besides constituting an important tool to understand the relationships between contamination and the involved environmental variables.

O objetivo deste trabalho foi avaliar as densidades de coliformes totais e termotolerantes, em água de cultivo de ostra de Cananeia, SP, e correlacionar estas densidades com variáveis ambientais e as variações das marés. Foram coletadas amostras de água superficial em duas condições de maré (sizígia e quadratura) de três áreas do Município de Cananéia (Mandira, Itapitangui e Cooperostra). As três áreas estudadas apresentaram boas condições para cultivo, quanto à densidade de coliformes. Diferenças significativas foram registradas entre as condições de marés quanto à concentração total de coliformes; no entanto, o mesmo procedimento não se aplicou para coliformes termotolerantes. Nenhuma correlação foi observada entre a temperatura da água, o pH e as concentrações de coliformes total e termotolerantes. As densidades de coliformes correlacionaram-se positivamente com a pluviosidade e negativamente com a salinidade. O número de coliformes foi significativamente diferente nas marés de sizígia e de quadratura. O simples diagnóstico das condições ambientais é insuficiente para avaliar a qualidade da água de cultivo de ostras. Um programa de monitoramento contínuo de áreas cultivadas é necessário tanto para avaliar o potencial dessas águas, como para garantir o consumo seguro de frutos do mar, além de constituir-se como instrumento importante para a compreensão das relações entre a contaminação por coliformes e as variáveis ambientais envolvidas.
Densidade de coliformes em águas de cultivo de ostras e sua relação com fatores ambientais
Keywords: Crassostrea; contaminação; microbiologia; análise de componentes principais; colifirmes totais e termotolerantes; Crassostrea; contamination; microbiology; principal component analysis; total and thermotolerant coliforms